The role of 18F–NaF PET/CT in metastatic bone disease - Araz, Mine (J Bone Oncol, 2015)
AIM: To investigate the role of 18F–NaF PET/CT and compare it with 99m Tc-MDP whole body bone scintigraphy and 18F-FDG PET/CT in detecting the extent of metastatic bone disease and to present our first experience with 18F–NaF PET/CT in our country. MATERIALS AND METHODS: A total of 37 histopathologically proven cancer patients (22 male, 15 female) with bone metastasis detected on Tc-99m MDP whole body bone scan were prospectively enrolled Cebeci, following ethics committee approval. 18F–NaF PET/CT was performed to the participants in Ankara University Medical Faculty Nuclear Medicine Department for evaluation of symptomatic skeletal sites which were negative on Tc-99m MDP whole body bone scan. A lesion based comparison was made between 18F–NaF PET/CT and Tc-99m MDP whole body bone scan for each patient and between 18F–NaF PET/CT and 18F-FDG PET/CT in 12/37 patients. RESULTS: The number of lesions demonstrated by 99m Tc-MDP bone scan and 18F–NaF PET/CT was equal in 4/37 (%11) of the cases. 18F–NaF PET/CT showed a greater number of pathological foci in 89% of participants. 18F–NaF PET/CT was able to show both lytic and blastic lesions and small lesions were better visualized due to the advantage of sectional imaging with much better resolution and higher target/background ratio. 18F–NaF PET/CT demonstrated a greater number of metastases in 10/12 (83%) of the patients when compared to 18F-FDG PET/CT. In the other two patients, bone metastasis could be demonstrated only by 18F–NaF PET/CT. The uptake of 18F-FDG was variable in blastic lesions and cranial bone involvement was missed by 18F-FDG PET/CT in some cases due to physiological brain metabolism. CONCLUSION: Although further prospective clinical studies in specific cancer populations are indicated to set the place of 18F–NaF PET/CT in diagnostic scheme, the results of this pilot study from our country support the superiority of 18F–NaF PET/CT in investigation of bone metastasis over 99mTc-MDP bone scan and 18F-FDG PET/CT in various malignancies. 18F–NaF PET/CT is coming forward as a single step bone seeking study, considering all the advantages, but especially potential of detecting occult metastases and reliably directing patient management.